Assessing the impact of small amounts of water and iron oxides on adhesion in the wheel/rail interface using High Pressure Torsion testing. (July 2019) - Buckley-Johnstone, L.E.; Trummer, G.; Voltr, P.; Meierhofer, A.; Six, K.; Fletcher, D.I.; Lewis, R.
Abstract: A new High Pressure Torsion (HPT) set-up has been developed for assessing the effect of third body materials in the wheel/rail interface in a representative and controlled manner. In this study the technique has been used to investigate the effect of small amounts of water and iron oxides mixtures when subjected to different contact pressures. HPT tests showed reduction in adhesion relative to a dry contact when testing with small amounts of water and/or oxides, however sustained low adhesion (μ<0.05) was not produced. To aid interpretation of the results a model has been developed to explore the behavior encountered when testing with water and iron oxide mixtures. The model relates the shear properties of water and oxide mixtures (with increasing solid content) to a predicted adhesion. The model shows a narrow window of water to oxide fraction is required for reduced adhesion, particularly on rough surfaces, and this correlates with the behavior observed. Highlights: Significant reduction of friction (over dry conditions) was observed when applying low amounts of water to the interface. Tribological testing guided the identification of parameters key to the low adhesion mechanisms. The model can estimate adhesion levels in the presence of different water and iron oxide mixtures. The adhesion model outputs are in accordance with the experience that low adhesion is observed with low amounts of water. This reduction of adhesion is limited to a narrow range of conditions.